Upconversion Nanoparticles for Cancer Therapy. Issue 12 (8th December 2022) - Li, Yang; Chen, Guanying
Abstract : Cancer Therapies In article number 2200092, Yang Li and Guanying Chen summarize the fundamental roles of Lanthanidedoped upconversion nanoparticles in cancer therapy and highlight types of cell death caused by excess reactive oxygen species and also highlight cutting‐edge applications in multimode cancer therapy and imaging‐guided cancer therapy.